PENGARUH KONFLIK ISRAEL-IRAN TERHADAP PASAR ENERGI DUNIA DAN IMPLIKASINYA PADA PORTOFOLIO INVESTASI - Aulia, Arti Mirza; Maharani, Diva Damai; R. Pandin, Maria Yovita (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
The Israel-Iran conflict has a significant impact on the global energy market, especially through the Strait of Hormuz, a strategic route for the world's oil supply. This study analyzes the effect of the conflict on the energy market and its impact on the energy sector investment portfolio, using data from energy companies in Indonesia for the period 2019-2023. Quantitative research method was applied, and the analysis was conducted using SPSS 26 through descriptive test, normality test, and ANOVA. The results of the normality test show that the Israel-Iran Conflict variable is not normally distributed, while the World Energy Market and Investment Portfolio variables are normally distributed. The ANOVA test shows that the Israel-Iran conflict has no significant effect on the average change in the energy market and investment portfolio. In contrast, there were significant differences in the World Energy Market and Investment Portfolio between groups, suggesting that other factors influenced these two variables. These results indicate the importance of considering factors other than the Israel-Iran conflict in energy investment strategies.